Assessment of Efficacy and Complications of Endovascular Interventions for Critical Limb Ischemia in Germany: A Nationwide Study - Bastian, Moritz B.; Scheschenja, Michael; Wessendorf, Joel; König, Alexander Marc; Jedelská, Jarmila; Nadjiri, Jonathan; Mahnken, Andreas H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Purpose Endovascular interventional radiological procedures have become the mainstay for the treatment of critical limb ischemia (CLI) due to arterial stenosis or occlusion. Open surgical or endovascular procedures, such as percutaneous transluminal angioplasty (PTA) or stenting can be used as a treatment strategy. The aim is to evaluate the success and major complication rates of interventional radiology treatments for CLI in Germany in 2021, and to compare these results with internationally published data.Materials and Methods Data for PTA and stenting in CLI for 2021 was obtained from the quality management system of the German Society of Interventional Radiology (DeGIR). 16 393 PTA procedures, 701 stenting procedures, and 8110 combined procedures were documented for 2021. Data was analyzed for technical and clinical success rates, as well as major complication rates documented mainly as major bleeding, distal embolization, and aneurysm formation.Results PTA had technical and clinical success rates of 96.3 % and 92.33 %, respectively. Stenting had technical and clinical success rates of 98.7 % and 96.15 %, respectively. PTA and stenting combined had success rates of 98.71 % and 96.91 %, respectively. The major complications were mainly: major bleeding (PTA: 0.40 %; stenting: 1.28 %; PTA and stenting: 0.54 %), distal embolization (PTA: 0.48 %; stenting: 1 %; PTA and stenting: 0.96 %), and aneurysm formation (PTA: 0.19 %; stenting: 0.43 %; PTA and stenting: 0.19 %). All procedures showed high technical and clinical success rates, while the complication rates were low.Conclusion Interventional radiologists in Germany perform effective and safe treatment for CLI, achieving outcomes that tend to surpass internationally published data.Key points Citation Format
Keywords: arteriosclerosis; stenosis; stenting; percutaneous transluminal angioplasty; critical limb ischemia